ANALISIS PERHITUNGAN PPH PASAL 21 KARYAWAN BERDASARKAN UU NO.36 TAHUN 2008 DAN UU HARMONISASI PERATURAN PERPAJAKAN UU NO.7 TAHUN 2021 - Mardawati, Mardawati (Pusat Penerbitan dan Publikasi Ilmiah FEB-UMI, 2024)
This study raises the problem of calculation and comparison of Income Tax based on Law No. 36 of 2008 and Law No. 7 of 2021. The purpose of this study is to determine the calculations and comparisons made based on Law No. 36 of 2008 and Law No. 7 of 2021. The research method used in data collection is through library research and documentation. The analysis tool used in this study is to use the PPh Article 21 calculation format based on the Minister of Finance Regulation No. 101 / PMK.010 / 2016. The population in this study were all employees at PT. Bank Rakyat Indonesia (Persero) Tbk. KCP Sultan Alauddin with a sample size of 11 people. The results of the study on the calculation and comparison of Article 21 Income Tax based on Law No. 36 of 2008 and Law No. 7 of 2021 are that the tax burden that must be paid is lower with Law No. 7 of 2021 compared to the previous Article 21 Income Tax Law.